PENGARUH KINERJA KEUANGAN DAN KONDISI MAKRO EKONOMI TERHADAP NILAI PERUSAHAAN PADA SUB SEKTOR TELEKOMUNIKASI YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2019 - 2023 - Rahayu, Dini Dwi Asry; Hapsari, Andriyani (JURNAL ILMIAH EKONOMI, MANAJEMEN, BISNIS DAN AKUNTANSI, 2025)
. This research aims to analyze the influence of financial performance and macroeconomic conditions on the value of companies in the telecommunications sub sektor listed on the Indonesia Stock Exchange. The observation period used is from 2019 to 2023. The independent variables studied are financial performance measured by return on equity (ROE) and macroeconomic conditions measured by inflation, while the dependent variable is the company's value measured by price to book value (PBV). The type of this research is quantitative with an associative approach using panel data regression analysis techniques. The research population includes 22 companies in the telecommunications sub sektor, and by using the purposive sampling method, a sample of 9 companies was obtained. The research results indicate that partially, financial performance (ROE) has a significant effect on company value (PBV) with a t-statistic value of 4.568924 > t-table 2.0180 and a significance value of 0.0000 < 0.05. Meanwhile, macroeconomic conditions (inflation) partially do not have an effect and are not significant on company value (PBV), as evidenced by a t-statistic value of -0.577563 < t-table 2.0180 and a significance value of 0.5666 > 0.05. However, simultaneously, financial performance and inflation have an effect and are significant on company value with an F-statistic value of 10.39659 > F-table 3.21994 and a significance value of 0.000215 < 0.05. The contribution of these two variables to the company's value is 29.92%, while the remainder is explained by other variables outside the scope of this research model.